The Cognitive Profiles of Poor Readers/Good Spellers and Good Readers/Poor Spellers in a Consistent Orthography: A Retrospective Analysis - Manolitsis, George; Georgiou, George K. (Preschool and Primary Education, 2015)
Reading and spelling are closely related to each other, but empirical evidence shows that they can also dissociate. The purpose of this study was to examine the cognitive profiles of good readers/poor spellers and poor readers/good spellers in a relatively consistent orthography (Greek). One hundred forty children were administered measures of phonological awareness, rapid automatized naming, phonological short-term memory, and orthographic knowledge in grades 1 and 2. Their performance in reading and spelling was assessed in grade 4. Two small groups of children exhibited dissociation between reading and spelling: seven children were identified as poor readers/good spellers and 11 children as good readers/poor spellers. The former group experienced severe deficits in both rapid naming and phonological awareness. The latter group experienced only mild deficits in orthographic knowledge. Although inefficient orthographic knowledge affects their spelling accuracy (Greek is inconsistent in the direction of spelling), it does not impact their reading fluency because they can recognize words by relying on partial cues.